Modulation of thrombomodulin-dependent activation of human protein C through differential expression of endothelial Smads - Sandusky, George; Berg, David T; Richardson, Mark A; Myers, Laura; Grinnell, Brian W (The Journal of biological chemistry, 2002)
Protein C is a plasma protease that in its active form plays a central role in the regulation of vascular function by modulating thrombosis, inflammation, and apoptosis. A central player in this pathway is the cytokine-regulated receptor thrombomodulin (TM), which functions as a co-factor for the thrombin-dependent generation of activated protein C. We have found that tumor necrosis factor-beta (TGF-beta)-dependent suppression of TM on endothelial cells is differentially regulated by endothelial Smad6s and Smad7. Overexpression of Smad6s resulted in activation of a TGF-beta reporter alone and enhanced TGF-beta response. Moreover, Smad6s overexpression suppressed TM and subsequently reduced activated protein C generation. Antisense inhibition of Smad6s expression enhanced the TM-dependent activation of protein C, whereas blocking the inhibitory Smad7 by antisense resulted in reduced TM-dependent activation of protein C. The effect of Smad6s appeared to be due, at least in part, to up-regulation of TGF-beta itself. Immunohistochemistry studies in normal versus atherosclerotic vessels showed that TM levels were suppressed in the endothelium over plaque. Consistent with the in vitro data, we found differential expression of Smad6s and Smad7 in normal versus atherosclerotic vessels, with Smad6s expression low in normal vessels but elevated in atherosclerotic vessels. In contrast, the opposite expression pattern was observed for Smad7. Overall, our results suggest that the relative balance of these intracellular Smads modulate the balance of endothelial function with regard to protein C activation.